Tackling Multiple-Drug-Resistant Bacteria With Conventional and Complex Phytochemicals - Suganya, Thangaiyan; Packiavathy, Issac Abraham Sybiya Vasantha; Aseervatham, G. Smilin Bell; Carmona, Areanna; Rashmi, Vijayaragavan; Mariappan, Subramanian; Devi, Navaneethan Renuga; Ananth, Devanesan Arul (Frontiers in Cellular and Infection Microbiology, 2022)
Emerging antibiotic resistance in bacteria endorses the failure of existing drugs with chronic illness, complicated treatment, and ever-increasing expenditures. Bacteria acquire the nature to adapt to starving conditions, abiotic stress, antibiotics, and our immune defense mechanism due to its swift evolution. The intense and inappropriate use of antibiotics has led to the development of multidrug-resistant (MDR) strains of bacteria. Phytochemicals can be used as an alternative for complementing antibiotics due to their variation in metabolic, genetic, and physiological fronts as well as the rapid evolution of resistant microbes and lack of tactile management. Several phytochemicals from diverse groups, including alkaloids, phenols, coumarins, and terpenes, have effectively proved their inhibitory potential against MDR pathogens through their counter-action towards bacterial membrane proteins, efflux pumps, biofilms, and bacterial cell-to-cell communications, which are important factors in promoting the emergence of drug resistance. Plant extracts consist of a complex assortment of phytochemical elements, against which the development of bacterial resistance is quite deliberate. This review emphasizes the antibiotic resistance mechanisms of bacteria, the reversal mechanism of antibiotic resistance by phytochemicals, the bioactive potential of phytochemicals against MDR, and the scientific evidence on molecular, biochemical, and clinical aspects to treat bacterial pathogenesis in humans. Moreover, clinical efficacy, trial, safety, toxicity, and affordability investigations, current status and developments, related demands, and future prospects are also highlighted.